Pottery Provenance in the Eastern Mediterranean Using Lead Isotopes. (3rd November 2015) - Renson, V.; Slane, K. W.; Rautman, M. L.; Kidd, B.; Guthrie, J.; Glascock, M. D.
Abstract : The lead isotope composition of 45 sherds of six different pottery wares from the Eastern Mediterranean and dating from the Late Hellenistic – Late Roman period is analysed and compared to data obtained on ceramics and clays from the Eastern Mediterranean. These sherds were previously analysed by neutron activation and the origin and relationship between the wares has been debated in the literature. The results show that lead isotopes support earlier hypotheses proposed based on NAA or answer questions left unanswered by NAA concerning the origin and relationships between these wares. The lead isotopic data complement the NAA and the results also confirm the effectiveness of lead isotope analysis in discriminating among different wares from production centres in the Eastern Mediterranean.